2008
DOI: 10.1039/b806192k
|View full text |Cite
|
Sign up to set email alerts
|

CuII binding sites located at His-96 and His-111 of the human prion protein: thermodynamic and spectroscopic studies on model peptides

Abstract: The prion protein (PrP) is a Cu(2+)-binding cell-surface glycoprotein. Using PrP peptide fragments, by means of potentiometric, spectroscopic and thermodynamic techniques, we have shown that Cu(2+) ions bind to the region comprising His-96, His-111 and the octarepeat domain within residues 60-91. Cu(2+) may bind in different modes, which strongly depend both on His position within the peptide sequence and on the adjacent residues. We have used a series of protected oligopeptides having His at the C- or the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 37 publications
3
46
0
Order By: Relevance
“…In the CD spectrum (Fig. 3) the charge transfer contribution around the 290 nm seems also to support an increasing contribution from the Cu-N transitions [21][22][23] starting from CuH À1 L species. Notably, large CD perturbation is observed in concomitance with the transition from CuH À1 L to the CuH À2 L species, while this latter show similar CD behavior to the CuH À3 L and CuH À4 L species.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the CD spectrum (Fig. 3) the charge transfer contribution around the 290 nm seems also to support an increasing contribution from the Cu-N transitions [21][22][23] starting from CuH À1 L species. Notably, large CD perturbation is observed in concomitance with the transition from CuH À1 L to the CuH À2 L species, while this latter show similar CD behavior to the CuH À3 L and CuH À4 L species.…”
Section: Resultsmentioning
confidence: 84%
“…The CD features that are observed around 290 nm should be assigned to amide to copper(II) charge transfers [21][22][23]. In turn, features assignable to His to Cu(II) CT should fall in the 330-350 nm range [23].…”
Section: Resultsmentioning
confidence: 98%
“…[67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated. A comparison of the thermodynamic stabilities of the histidinecontaining fragments revealed that the peptides that encompass the amino acid sequences outside the octarepeat domain are even more efficient chelators of copper(II) than the single octarepeat fragments.…”
Section: Introductionmentioning
confidence: 71%
“…At pH 7.4 three metal-coordination modes have been found so far within the tetraoctarepeat domain: [81] Two copper(II) binding sites, centred around His96 and His111, have also been found for the amyloidogenic PrP region, [67,69,78] with His111 having a higher affinity for copper(II). [72,73,75,90,91,108] (N im ,N À ,N À ) is the main metal-binding mode experienced by Cu 2+ , although there is no general agreement on the contribution of additional donor atoms. [72,74,89,90,[93][94][95][96][97][98][109][110][111] Structural rearrangement of the N-terminus caused by copper(II) binding has also been studied but conflicting results have been reported for peptides that contain different domains.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation